No defensive role of ants throughout a broad latitudinal and elevational range of a cactus - Alma, Andrea Marina (2015)
Defensive mutualisms mediated by extrafloral nectaries are particularly variable, their net results may change with seasons, communities and environmental contexts. Particularly, an environmental factor that can promote changes in outcomes of ant-plant interactions is elevation in mountainous regions. We tested whether (1) the interaction between the cactus Opuntia sulphurea and ant visitors of extrafloral nectaries is a defensive mutualism; and (2) ant-plant interaction outcomes vary with elevation as a result of changes in herbivory rate and ant activity. To evaluate if the outcome of interactions was consistent at two extremes of the range distribution of O. sulphurea, we performed an ant-exclusion experiment with plants at two growth conditions (natural or potted) in two sites with contrasting elevation (1235-1787 m asl) in a temperate region (Villavicencio Nature Reserve, Mendoza, Argentina), and in a tropical region (Huajchilla, La Paz, Bolivia). Although herbivory rate and ant visitation frequency increased with elevation, herbivore damage, plant reproductive success, and cladode growth rate were similar between plants excluded and non-excluded from ants among sites, geographic regions and growth conditions. These results do not support the hypotheses that the interaction between O. sulphurea and ants is a defensive mutualism, and that elevation affects the net outcome of this ant-plant interaction.